Virtual assistants in the family home. Understanding parents' motivations to use virtual assistants with their Child(dren). (February 2023) - Wald, Rebecca; Piotrowski, Jessica T.; Araujo, Theo; van Oosten, Johanna M.F.
Abstract: Virtual assistants (VA) like Siri, Alexa, or Google Assistant are becoming household names - especially for families with young children. Scientific inquiry studying this user population and their intention to use VAs at home, however, remains scarce. By bridging the Technology Acceptance Model, Uses and Gratifications theory, and the first proposition of the Differential Susceptibility to Media Effects Model, this study disentangles (1) different types of families with (2) different motivations for (3) different forms of VA-usage (i.e., parent only, child only, co-use). Cross-sectional survey data ( N = 305) from Dutch parents with at least one child between 3 and 8 years and a Google Assistant-powered smart speaker in their home show that (1) families mostly differ along parents' digital literacy skills, frequency of VA-use, trust in technology, and preferred degree of child media-mediation. (2) Hedonic motivation is key for parents to (3) co-use the VA together with their child(ren). New pathways for the methodological and theoretical study of technology use in families are highlighted. Developers can best anchor VA-application among families in aspects of enjoyment while scholars and policy makers might wish to consider additional meaningful intervention criteria for the future study and guidance of family VA-use practices. (197 words). Highlights: Families use virtual assistants in three ways: parent-/child-/co-usage. Internet literacy, use frequency, trust, and media mediation classifies families. Enjoyment motivates parents' intention for co-usage. Unique family types do not show unique use-motivations. Hedonic-utilitarian hypothesis connecting ease of use, enjoyment, and usefulness.